Understanding family childcare educators’ experiences in Alberta, Canada: a focus group study - Laura Woodman; Rhonda Breitkreuz; Rebecca Gokiert; Adam M. Galovan (International Journal of Child Care and Education Policy)
Abstract Given the unique challenges of offering childcare in home-based settings, specialized support is needed to help family childcare educators offer high-quality early learning and childcare. The purpose of this study was to increase understanding of the unique needs of home-based educators and identify supports based on educator and consultant perspectives. This study addresses the current gap within the Canadian early learning and childcare system in understanding family childcare educators’ experiences by asking the following questions: (1) What are the experiences of family childcare educators in Alberta? and (2) From educator and consultant perspectives, what are the factors that facilitate the ability to provide high-quality childcare in family childcare programs? A descriptive qualitative engaged research approach was used in this study. In focus groups, 26 experienced educators and consultants shared their perceptions of facilitators and barriers to high-quality family childcare. Our study highlights three areas for growth in Alberta’s childcare sector: the need for professional development targeted to the family childcare field, increased access to community connections and resources, and agency support enabling educators to take breaks. Family childcare educators have unique workplace strengths and challenges and require support from families, professional support systems, and policy makers to provide high-quality early learning and childcare.